The impact of a quality improvement project to standardize pain, agitation, and withdrawal assessments on the use of morphine and midazolam in the Pediatric Intensive Care Unit. Issue 4 (22nd February 2019) - Kongkiattikul, Lalida; Dagenais, Maryse; Ruo, Ni; Fontela, Patricia; Di Genova, Tanya; Zavalkoff, Samara
Summary: Background: This study aims to assess the impact of a quality improvement initiative to increase assessments of pain, agitation, and iatrogenic withdrawal syndrome, on the use of sedative and analgesic medication in a pediatric intensive care unit. Methods: This is a retrospective pre and post, observational, quality improvement study conducted in an 18‐bed medical‐surgical‐cardiac, tertiary intensive care unit. We included patients consecutively admitted from October 1 to March 31 (pre‐period 2015‐2016, post‐period 2016‐2017) who were mechanically ventilated beyond 48 hours. A multidisciplinary team, including a family advisor, implemented the following interventions using rapid "Plan‐Do‐Study‐Act cycles:" (a) standardized pain and sedation assessments, (b) standardized sedation goal setting, and (c) non‐pharmacological strategies to manage pain and agitation. We did not implement any specific sedation protocol. We used audit and feedback to reinforce change. Results: The post‐intervention phase started once sedation scores were documented q12h for >60% of patients. The groups (n = 45 per group) were similar regarding demographics, severity of illness, and mechanical ventilation duration, but different in length of intensive care stay. The cumulative dose of midazolam equivalent was significantly lower in the post‐intervention period (3.71 vs 2.65 mg/kg/mechanical ventilation day, P  = 0.009, 95% CI: −1.12 (−1.89, −0.31)). Morphine equivalent usage went from 3.51 to 2.57 mg/kg/mechanical ventilation day ( P  = 0.066, 95% CI: −0.67 [−1.44, 0.05]). There were no significant pre‐post‐differences in the use of other sedative agents, rates of iatrogenic withdrawal syndrome or severe pain, nor medication cost. Conclusion: Implementation of a multifaceted QI project was successful at increasing standardized assessments of pain and agitation, and was associated with a significant reduction in midazolam use. We also observed a decrease in morphine use without increasing rates of severe pain. Incidence of iatrogenic withdrawal syndrome and cost were unchanged.